A importância do ato de brincar na prática pedagógica do professor de educação infantil na Creche Municipal Casulo Nilma Assad - NASCIMENTO, Rosiane Cristina Costa (2020)
The research presented here has as main objective to know how the act of playing can be important in the pedagogical practice of the nursery school teacher of the Municipal School of Infant and Elementary Education Casulo Nilma Assad. The problematic approach was instituted in: problematic as the ludic activities in particular the act of playing can be fundamental and important for the development of a learning with more quality in the education of children? How can this act provide learning resources to Nilma Assad Daycare students? Regarding the methodological procedures, the study brings a qualitative research and also a case study in a municipal institution of the city of Boni9to Pará, with data collection through a semi-structured questionnaire to be answered individually. The sample was formed by 2 (two) teachers of the municipal education network and active in Early Childhood Education. The research is based on the studies of authors such as Kishimoto (1994), Kami (2001), Piaget (1971), Wajskop (2007) and Vasconcelos (1994) among others. The results show that games and games when used in learning can be an excellent teaching tool for the teacher and can help him to develop activities that help him in the process of teaching and learning. The research findings show that these educational methodologies break down any and all paradigm of a traditional education providing much more dynamism and quality education.